2010
DOI: 10.1111/j.1476-5381.2010.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of the K+ channel KCNQ genes in human arteries

Abstract: BACKGROUND AND PURPOSEKCNQ-encoded voltage-gated potassium channels (Kv7) have recently been identified as important anti-constrictor elements in rodent blood vessels but the role of these channels and the effects of their modulation in human arteries remain unknown. Here, we have assessed KCNQ gene expression and function in human arteries ex vivo. EXPERIMENTAL APPROACHFifty arteries (41 from visceral adipose tissue, 9 mesenteric arteries) were obtained from subjects undergoing elective surgery. Quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
137
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(148 citation statements)
references
References 32 publications
10
137
1
Order By: Relevance
“…There are five Kv7 isoforms (Kv7.1-Kv7.5) of which Kv7.1, Kv7.4, and Kv7.5 are consistently expressed within VSM, where the predominant molecular architecture is a Kv7.4/Kv7.5 heterotetramer (2,3). Activation of Kv7 channels produces relaxation of numerous arteries (4)(5)(6)(7)(8), whereas blockade of Kv7 channels results in contraction of vessels at rest (7,(9)(10)(11) or an inhibition of endogenously derived vasorelaxations (2,(11)(12)(13). In addition, molecular reduction of Kv7.4 reduces responses to various Gs-coupled vasodilators in a number of arteries (2,11).…”
mentioning
confidence: 99%
“…There are five Kv7 isoforms (Kv7.1-Kv7.5) of which Kv7.1, Kv7.4, and Kv7.5 are consistently expressed within VSM, where the predominant molecular architecture is a Kv7.4/Kv7.5 heterotetramer (2,3). Activation of Kv7 channels produces relaxation of numerous arteries (4)(5)(6)(7)(8), whereas blockade of Kv7 channels results in contraction of vessels at rest (7,(9)(10)(11) or an inhibition of endogenously derived vasorelaxations (2,(11)(12)(13). In addition, molecular reduction of Kv7.4 reduces responses to various Gs-coupled vasodilators in a number of arteries (2,11).…”
mentioning
confidence: 99%
“…Kv7 voltage-activated potassium channels are expressed in many excitable cell types, including neurons, cardiac, skeletal, vascular, and visceral myocytes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) where they function to stabilize resting membrane potential and restrict cellular excitability (6,16). The five members of the Kv7 family (Kv7.1-Kv7.5) are encoded by five mammalian genes (KCNQ1-5), and the individual gene products assemble as homomeric or heteromeric tetramers to form functional channels (17).…”
mentioning
confidence: 99%
“…KCNQ1, KCNQ4, and KCNQ5 genes are expressed in the murine, rat, and human vasculature (10,13,18,19), with the KCNQ4 transcripts being most abundant in mouse and rat, and an approximately equal expression of KCNQ1, KCNQ3, KCNQ4, and KCNQ5 in human arteries (13). Pharmacological screening of functional channels in vascular smooth muscle cells suggested that Kv7.4 and/or Kv7.5 are the predominant functional isoforms (10,11,13,18). This conclusion was drawn based on the expression pattern and the ability of retigabine and flupirtine, selective Kv7.2-7.5 channel activators, to enhance Kv7 currents in freshly isolated vascular myocytes and to relax constricted arteries (10,11,13,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Voltage-gated potassium channels (K V ) have been implicated in the control of the coronary circulation and reactive hyperemia, 1,2 but little is known about the specific molecular components. Kv channels encoded by KCNQ1-5 (K V 7.1-K V 7.5) are important regulators of the smooth muscle resting membrane potential and contractility in several different rodent and human arteries, [3][4][5][6][7][8][9][10][11] which are known to be compromised in animal models of primary and secondary hypertension. 3,6 These channels, in particular K V 7.4, are also functional end points in β-adrenoceptor-mediated relaxations.…”
mentioning
confidence: 99%